For this case we have the following equation:
![2x + 5 = -x + (- 1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iaiiopqlf2fljxseouwmny586gsq66y8kr.png)
Below are the correct steps to solve:
We eliminate the parenthesis taking into account that
![+ * - = -](https://img.qammunity.org/2020/formulas/mathematics/high-school/xk4qa3ktexp4l9yhhbslqi31fm79qsog59.png)
![2x + 5 = -x-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zhm08ax8szqbwhgx2hnzlpgzq1h3c10agx.png)
We add "x" to both sides of the equation:
![2x + x + 5 = -x + x-1\\3x + 5 = -1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fhcfitftupnz2vpd5emqan9tmeufd46ju3.png)
We subtract 5 from both sides of the equation:
![3x + 5-5 = -1-5\\3x = -6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o9q815htaw5jcil5a5jxqsxp1hatmx567b.png)
We divide by 3 on both sides of the equation:
![x = \frac {-6} {3}\\x = -2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1in49p08z5g7zgem6k1mewt1hzulbowzdf.png)
ANswer:
![x = -2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nmlwryt0el3w782l1kh8ntwo5z9jn123en.png)